2013
DOI: 10.1084/jem.20121527
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation inhibits AML growth and survival: a potential therapeutic approach

Abstract: Activating Notch with a Notch agonist peptide induces apoptosis in AML patient samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 60 publications
9
130
0
Order By: Relevance
“…In another study the same authors suggested that caspase-3 activation and PARP inactivation may play a role in prednisolone-and l-asparaginase-induced apoptosis, but are not essential to vincristine-and daunorubicin-induced apoptosis [15]. Kannan et al reported that Notch 1-related transcription factors stimulate higher expression of PARP-1 messenger RNA and thus induce apoptosis in B-ALL cell lines, an effect not seen in T-ALL cell lines [20]. Pottier et al stated that lower SMARCB1 expression increased prednisolone resistance in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…In another study the same authors suggested that caspase-3 activation and PARP inactivation may play a role in prednisolone-and l-asparaginase-induced apoptosis, but are not essential to vincristine-and daunorubicin-induced apoptosis [15]. Kannan et al reported that Notch 1-related transcription factors stimulate higher expression of PARP-1 messenger RNA and thus induce apoptosis in B-ALL cell lines, an effect not seen in T-ALL cell lines [20]. Pottier et al stated that lower SMARCB1 expression increased prednisolone resistance in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Notch agonists were shown to enhance p53 expression along with BCL2 downregulation and growth inhibition of AML cells. 93 …”
Section: Aml With Chromosomal Translocationsmentioning
confidence: 99%
“…FLT3 is already known as a frequently mutated oncogene in AML, whereas the role of NOTCH2 in this disease is not well understood, although decreased NOTCH2 expression has been linked to AML in 2 reports. 35,36 Cloning and sequencing analysis identified several aberrant splice variants of NOTCH2 and FLT3 that resulted from either skipping of $1 exon or activation of cryptic splicing sites. All these splicing alterations created transcripts that encoded proteins, as demonstrated through expression of NOTCH2-Va, NOTCH2-Vb, FLT3-Va, and FLT3-Vb splice variants in HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%